The Effect Hormone Cytokynin and Giberelin On Maize Growth (Zea mays L.) - Jumaria Nasution,; Friska, Meiliana (Jurnal Online Pertanian Tropik, 2020)
Maize is important food comodity in indonesia beside rice. In its devolepment,maize does not only function as food for human, but also asa staple in animal feed industry and other needs, to meet market demand for increased maize production,it is in necessary to improve cultivation methods with the application of growth regulators,namely by used giberellin and cytokinins.Giberellin is hormone that affects plant growth in the germination and flowering phases while cytokinins play arole in cell elongation. The aim of this study was to evaluate the effect of gibberelin and cytokinins on stem height, leaf lenght panicle land.This study used a completely randomized design with two factors, the concentration of giberellin and cytokinin 0, 10,20,50 ppm.Based on the data analysis below combiation had a significant effect on the stem height(P2C1).Cytokinin at concentration of 25 and giberelin 10 ppm increase the stem height(. The combination cytokynin 50 ppm and giberellin 50 ppm (P3C3) affect leaf lenght and lengt of panicle maize.